Recreio escolar em cena: a mediação por meio dos jogos teatrais - Buriti, Alexsandra Silva Oliveira (2020)
Children, as well as adults go through small torments during their school trajectory, I was particularly the victim of the famous “At the time of leaving I catch you”, I was physically attacked right at recess, I arrived in the room crying and not for that reason. teacher asked why she was crying and scratching. Faced with this and other events, I became the teacher who looks and listens very lovingly to what students say about school recess and I use theatrical games as an ally for this approach. Therefore, I started to problematize the effects of theatrical games in this space that is also educational and that was full of conflicts. So I started to problematize the effects that theatrical games could have on school recess and consequently with their teachers in the classroom. I successfully achieved the general objective, which was to analyze the impact of the theatrical game on the school break, promoting a change in the interaction between the students of the Municipal School of Elementary Education Cícera da Silva Sousa, located in Barra de Santa Rosa, Paraíba state. The starting point of the research is justified in the current school scenario, where the relationships of interaction between students within the classroom and, mainly, in school recess, end up in some way bumping into teaching-learning and living together. It is a participatory research with a qualitative approach and divided into five chapters, in chapter one entitled as Welcome: Round of conversation. In it I describe details of my childhood until I reached the master's degree. In chapter two, “Backstage” I describe all the theoretical foundation that I used to compose the workshops / classes that are the authors: Augusto Boal, Viola Spolin and Olga Reverbel that address theatrical games. In the third chapter, “Playing another game: I trade marbles for a conversation”, I bring all the strategies I used to approach the students during the research. In "Outside the walls of the school" I report all the themes of the workshops / classes meetings as well as how the trip to the theater impacted our creations. Finally, the fifth chapter, “Memories, memories of yesterday”, where I analyze all the data I observed in the research, which was surprising and enriching. I used as data collection the interviews, audio recordings, notes in the logbook and photographic record that appear throughout the dissertation. The focus group had twenty students, from the second to the fifth year, enrolled in hours opposite the workshops / classes.